2016
DOI: 10.3343/alm.2016.36.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Bacteremia Due toRoseomonas mucosa

Abstract: Roseomonas is a genus of pink-pigmented nonfermentative bacilli. These slow-growing, gram-negative cocobacilli form pink-colored colonies on sheep blood agar. They differ from other pink-pigmented nonfermenters, including Methylobacterium, in morphology, biochemical characteristics, and DNA sequence. Roseomonas strains are rarely isolated in clinical laboratories; therefore, we report two cases in order to improve our ability to identify these pathogens. We isolated two strains of Roseomonas mucosa from the ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Among the bacterial pathogens identified, the genus Roseomonas was dominant in all the wastewater samples. Roseomonas species are now gradually being referred to as evolving opportunistic pathogens for their connection to human infectious diseases [73,74,75], and are mainly observed in patients with compromised immune systems [74,75]. The occurrence of this genus in higher percentages indicates that hospitals in the area probably accommodate patients with different health histories (HIV, psychiatric, and cancer), judging from the higher values obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Among the bacterial pathogens identified, the genus Roseomonas was dominant in all the wastewater samples. Roseomonas species are now gradually being referred to as evolving opportunistic pathogens for their connection to human infectious diseases [73,74,75], and are mainly observed in patients with compromised immune systems [74,75]. The occurrence of this genus in higher percentages indicates that hospitals in the area probably accommodate patients with different health histories (HIV, psychiatric, and cancer), judging from the higher values obtained.…”
Section: Discussionmentioning
confidence: 99%
“…In general, R.mucoca was resistant to β-lactam antibiotics, such as piperacillin-tazobactam, ampicillin, extended spectrum cephalosporins (cefrazidime, cefepime) and colistin, while it was full susceptibility to aminoglycosides (amikacin, gentamicin) and fluoroquinolones (levofloxacin, ciprofloxacin), and usually susceptible to carbapenems (imipenem, meropenem) [ 2 , 7 9 ]. Consistent to our results, the previous case series reported that 100% of R.mucoca isolated was resistant to piperacillin-tazobactam [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…infection Reference Age (yr)/Sex Infection Underlying disease Treatment Outcome Tsai S et al, 2012 [ 19 ] 48/M Peritonitis IgA nephropathy-related end-stage renal disease Day1–6:cephalosporin Day7–18:ciprofloxacin Day19–72:cefazolin and gentamicin Recovered Boyd MA et al, 2012 [ 8 ] 19/M Peritonitis Chronic renal failure, AIDS Cycling peritoneal dialysis (CCPD) Failure. Ece G et al, 2013 [ 16 ] 30/M Abscess formation Cranial fracture Remove the cranioplasty Recovered Al-Anazi et al, 2013 [ 20 ] 41/F Bacteremia T-lymphoblastic lymphoma Day1–4:Piperacillin-tazobactam 4.5 g IVq 8 h Day4–14:imipenem and amikacin Ciprofloxacin Recovered Kaore NM et al, 2014 [ 21 ] 37/M (Community acquired secondary bacterial infections) Pulmonary tuberculosis Amikacin and Cefoperazone/Sulbactam Recovered Michon AL et al, 2014 [ 17 ] 3/M Bacteremia Acute lymphoblastic leukemia Day1–4:piperacillin-tazobactam Day7–14:cefixime Recovered Kim KY et al, 2015 [ 7 ] 74/M Infectious spondylitis with bacteremia Compression fractures of the thoracic and lumbar spine Day4–7:intravenous cefazolin Day8–14:ceftazidime His back pain improved Kim KY et al, 2016 [ 2 ] 84/F Bacteremia Cholecystitis and chol-angitis Day4–6:cefotaxime and metroni-dazole combination Recovered (no signs of infection) Kim KY et al, 2016 [ 2 ] 17/M Bacteremia Acute myeloid leukemia ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their low pathogenicity, Roseomonas species rarely cause infections in humans; thus, its clinical features are not yet fully understood. To elucidate the clinical characteristics of Roseomonas bacteremia in children, we reviewed previous literature ( Table 2 ) [ 8 , 9 , [14] , [15] , [16] , [17] , [18] ]. A search of MEDLINE from its inception in 1996 revealed only 12 such cases.…”
Section: Discussionmentioning
confidence: 99%